2018
DOI: 10.1016/j.ejogrb.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Designing a lifestyle intervention to reduce risk of type 2 diabetes in postpartum mothers following gestational diabetes: An online survey with mothers and health professionals

Abstract: A walking programme, recipe ideas and weight monitoring may be useful components when designing a postpartum lifestyle intervention. Barriers to engagement are evident and the intervention should allow women to engage at a time that is appropriate for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Lacking knowledge on when to safely resume exercise after childbirth and the health consequences of pregnancy complications were barriers for postpartum women especially in those who had a pregnancy complicated by GDM or pre‐eclampsia 44,49,54 . Similarly, HPs believed that women were unaware of the benefits of physical activity, the importance of postpartum dietary modifications and weight control in reducing future risk of type 2 diabetes 50,58,59 . In one study, HPs themselves reported lacking knowledge of the relationship between GDM and diabetes mellitus (DM) and the role of dietary habits in the progression of GDM to DM 59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacking knowledge on when to safely resume exercise after childbirth and the health consequences of pregnancy complications were barriers for postpartum women especially in those who had a pregnancy complicated by GDM or pre‐eclampsia 44,49,54 . Similarly, HPs believed that women were unaware of the benefits of physical activity, the importance of postpartum dietary modifications and weight control in reducing future risk of type 2 diabetes 50,58,59 . In one study, HPs themselves reported lacking knowledge of the relationship between GDM and diabetes mellitus (DM) and the role of dietary habits in the progression of GDM to DM 59 …”
Section: Resultsmentioning
confidence: 99%
“…HPs similarly reported that women did not prioritise their health after childbirth, believing that they did not need to care for their own health anymore now that the baby was no longer part of their body. HPs also face time constraints, in that they felt they did not have enough time during consultation to support women with postpartum weight management 50 …”
Section: Resultsmentioning
confidence: 99%
“…Our survey of 106 healthcare professionals showed that 80% (17/21) of midwives and about 50% (11/21) of the obstetricians were unsure of the future risk of type 2 diabetes after gestational diabetes. 17 This further hinders provision of interventions to prevent type 2 diabetes in the postnatal period. Three-quarters of mothers (50/67) were interested in continuing metformin after delivery to prevent type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to improve physical activity among women with past GDM continue to be challenging for long-term behavior change. 33 Social support, 34 including partner 35 and peer support, 36 and walking programs 37 have been recommended for women with past GDM. Diabetes educators should refer women with past GDM to community resources that offer social support for physical activity.…”
Section: Discussionmentioning
confidence: 99%